American Exceptionalism and the Legacy of Vietnam - McCrisken, Trevor. author. aut Link
IX, 237 p.
Keywords: American Exceptionalism and the Legacy of Vietnam examines the influence of the belief in American exceptionalism on the history of U.S. foreign policy since the Vietnam War. Trevor B. McCrisken analyzes attempts by each post-Vietnam U.S. administration to revive the popular belief in exceptionalism both rhetorically and by pursuing foreign policy supposedly grounded in traditional American principles. He argues that exceptionalism consistently provided the framework for foreign policy discourse but that the conduct of foreign affairs was limited by the Vietnam syndrome.